Virological response and resistance among HIV-infected children receiving long-term antiretroviral therapy without virological monitoring in Uganda and Zimbabwe: Observational analyses within the randomised ARROW trial. - Alexander J Szubert; Andrew J Prendergast; Moira J Spyer; Victor Musiime; Philippa Musoke; Mutsa Bwakura-Dangarembizi; Patricia Nahirya-Ntege; Margaret J Thomason; Emmanuel Ndashimye; Immaculate Nkanya; Oscar Senfuma; Boniface Mudenge; et al. (PLoS Medicine, 2017)
Background Although WHO recommends viral load (VL) monitoring for those on antiretroviral therapy (ART), availability in low-income countries remains limited. We investigated long-term VL and resistance in HIV-infected children managed without real-time VL monitoring. Methods and findings In the ARROW factorial trial, 1,206 children initiating ART in Uganda and Zimbabwe between 15 March 2007 and 18 November 2008, aged a median 6 years old, with median CD4% of 12%, were randomised to monitoring with or without 12-weekly CD4 counts and to receive 2 nucleoside reverse transcriptase inhibitors (2NRTI, mainly abacavir+lamivudine) with a non-nucleoside reverse transcriptase inhibitor (NNRTI) or 3 NRTIs as long-term ART. All children had VL assayed retrospectively after a median of 4 years on ART; those with >1,000 copies/ml were genotyped. Three hundred and sixteen children had VL and genotypes assayed longitudinally (at least every 24 weeks). Overall, 67 (6%) switched to second-line ART and 54 (4%) died. In children randomised to WHO-recommended 2NRTI+NNRTI long-term ART, 308/378 (81%) monitored with CD4 counts versus 297/375 (79%) without had VL <1,000 copies/ml at 4 years (difference = +2.3% [95% CI -3.4% to +8.0%]; P = 0.43), with no evidence of differences in intermediate/high-level resistance to 11 drugs. Among children with longitudinal VLs, only 5% of child-time post-week 24 was spent with persistent low-level viraemia (80-5,000 copies/ml) and 10% with VL rebound ≥5,000 copies/ml. No child resuppressed <80 copies/ml after confirmed VL rebound ≥5,000 copies/ml. A median of 1.0 (IQR 0.0,1.5) additional NRTI mutation accumulated over 2 years' rebound. Nineteen out of 48 (40%) VLs 1,000-5,000 copies/ml were immediately followed by resuppression <1,000 copies/ml, but only 17/155 (11%) VLs ≥5,000 copies/ml resuppressed (P < 0.0001). Main study limitations are that analyses were exploratory and treatment initiation used 2006 criteria, without pre-ART genotypes. Conclusions In this study, children receiving first-line ART in sub-Saharan Africa without real-time VL monitoring had good virological and resistance outcomes over 4 years, regardless of CD4 monitoring strategy. Many children with detectable low-level viraemia spontaneously resuppressed, highlighting the importance of confirming virological failure before switching to second-line therapy. Children experiencing rebound ≥5,000 copies/ml were much less likely to resuppress, but NRTI resistance increased only slowly. These results are relevant to the increasing numbers of HIV-infected children receiving first-line ART in sub-Saharan Africa with limited access to virological monitoring. Trial registration ISRCTN Registry, ISRCTN24791884.